PERHITUNGAN MARKET VALUE ADDED (MVA) UNTUK MENILAI KINERJA KEUANGAN PADA PERUSAHAAN SUB-INDUSTRI DEPARTMENT STORE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sri Rani Fauziah; Rizki Ramadhan; Mutia Arfiani; Rismadi Rismadi; Meutia Handayani; Totok Rudianto; Emilda Kadriyani; Hilmi Hilmi; Irene Maulana Harahap (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to calculate MarkettValue Added (MVA) to assess the performance of sub-industrial department store companiesslisted on the Indonesia Stock Exchange during the 2018-2021 period. This research uses secondary data from three sub-industrial department store companies listed on the Indonesia Stock Exchange: PT. Matahari Department Store Tbk, PT. Ramayana Lestari Sentosa Tbk (RALS), and PT. Sona Topas Tourism Industry Tbk (SONA). For the analysis method for this research, the Market Value Added (MVA) method was chosen. The average company's financial performance is sufficient to produce market value, according to the results of measurement and analysis of financial data. This shows that the company made a mistake in increasing the value of genuine donors.